2001
DOI: 10.1046/j.1365-2141.2001.02777.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective ex vivo expansion of cytomegalovirus‐specific CD4+ and CD8+ T lymphocytes using dendritic cells pulsed with a human leucocyte antigen A*0201‐restricted peptide

Abstract: Summary. Adoptive transfer of ex vivo-generated cytomegalovirus (CMV)-specific T lymphocytes may be effective in preventing CMV disease in allogeneic haematopoietic stem cell transplantation (HSCT) recipients. We developed a procedure for expansion of CMV-specific T lymphocytes based on the antigen-presenting function of donor dendritic cells (DCs), pulsed with a human leucocyte antigen A*0201-restricted pp65 nonamer peptide. CMV-specific T lymphocytes were identified following induction of interferon g (IFN-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Current approaches are time consuming, require leukapheresis of donor for the generation of virus-specific T cells, use replicative competent virus, which is prohibited under current GMP regulations, or isolate CD4 ϩ or CD8 ϩ virus-specific T cells for adoptive transfer. [17][18][19][20][21][22] This study was conducted to circumvent limitations in the generation of virus-specific T-cell lines for adoptive transfer into allogeneic SCT recipients without impairing the functionality of the generated T-cell lines. To facilitate the enrichment of virusspecific T cells, the novel selection approach of the IFN-␥ secretion assay was applied to current GMP regulations, and a methodology was developed for the rapid enrichment and expansion of combined CD4 ϩ and CD8 ϩ CMV-specific T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current approaches are time consuming, require leukapheresis of donor for the generation of virus-specific T cells, use replicative competent virus, which is prohibited under current GMP regulations, or isolate CD4 ϩ or CD8 ϩ virus-specific T cells for adoptive transfer. [17][18][19][20][21][22] This study was conducted to circumvent limitations in the generation of virus-specific T-cell lines for adoptive transfer into allogeneic SCT recipients without impairing the functionality of the generated T-cell lines. To facilitate the enrichment of virusspecific T cells, the novel selection approach of the IFN-␥ secretion assay was applied to current GMP regulations, and a methodology was developed for the rapid enrichment and expansion of combined CD4 ϩ and CD8 ϩ CMV-specific T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo induction of CMV-specific T cells using CMV-infected autologous fibroblasts, EBV-infected B cells, or antigen-presenting cells (APCs) transduced with genes of interest as stimulator cells 13,[17][18][19] is an effective approach, but the potential biohazard resulting from the presence of live viruses may not be applicable to current good manufacturing practice (GMP) standards. Generating CMV-specific T cells using CMV peptidepulsed dendritic cells (DCs) 20,21 or CMV antigen-pulsed DCs 17,22 or using genetically modified APCs 18,19 is also an effective approach, but each is labor intensive and requires several weeks for the generation of a clinical product. Thus, alternative strategies are warranted to avoid the application of replicative virus during the stimulation procedure and to reduce the time required to generate sufficient CMV-specific T cells for adoptive transfer.…”
Section: Introductionmentioning
confidence: 99%
“…This could account at least in part for the lower anti-HHV-8 T-cell responses detected in healthy, HHV-8-seropositive individuals, [2][3][4] as compared to T-cell responses to EBV and CMV peptides in healthy, EBV-and CMV-seropositive persons. [36][37][38][39] Although the precise function of HHV-8 gB is unknown, a recent report shows that it is part of the virion and infected cell membrane, 49 in contrast to gB of EBV and MHV-68. 50,51 Indeed, gB may be important for HHV-8 infectivity and pathogenesis in that it binds to cell surface heparan sulfate molecules.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that human blood monocytederived DCs loaded with HIV-1, 35 EBV, 36,37 and human cytomegalovirus (CMV) 38,39 peptides are potent inducers of antiviral CD8 ϩ T-cell responses in PBMCs of individuals seropositive for these viruses. Therefore, we determined if autologous DCs loaded with gB 492-500 peptide were able to induce peptide-specific T-cell reactivity as compared to the conventional method of stimulation with peptide alone.…”
Section: T-cell Response To Gb 492-500 In Hla A*0201 Hhv-8 Seropositimentioning
confidence: 99%
“…This further confirms that peptideinduced CD8 T-cell lines recognize CMV antigens, as shown also by other groups. 19,[21][22][23] Also in this set of donors specificity was confirmed and frequency of specific T cells was remarkable. Nevertheless, we were unable to reduce phenotype variability, suggesting that more technologic improvements must be pursued.…”
Section: Functional Assays On Expanded T-cell Lines Obtained From Thementioning
confidence: 65%